2019
DOI: 10.1002/ijc.32689
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of meat, traditional and modern processed meat and colorectal cancer risk among the Moroccan population: A large‐scale case–control study

Abstract: The current study aimed to investigate the relationship between red and white meat subtypes, processed meat (divided into traditional “Khlii, Kaddid” and industrially processed meat) and colorectal cancer (CRC) risk, considering CRC subsites, in Moroccan adults. A case–control study was conducted including 2,906 matched case–control pairs recruited from the five largest university hospitals in Morocco. Dietary data were collected through a validated Food Frequency Questionnaire (FFQ). Multivariable odds ratios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Both red and white meat were reported to be among the most consumed products. We also observed a higher intake of red meat (pork, lamb, veal, beef) in CD patients compared to UC patients and higher intake of white meat (chicken, turkey, duck, rabbit) in UC patients than in CD patients, which should be further investigated because of the positive link between red and processed meat and GI cancers, such as gastric and colon cancer and colorectal cancer risk (Deoula et al, 2020;Kim et al, 2019), while white meat consumption is associated with a reduced risk of gastric cancer (Kim et al, 2019). In the latest Food and Crohn's Disease Exacerbation Study trial it has been noted that among patients with CD in remission, the level of red and processed meat intake was not correlated with time to symptomatic relapse (Albenberg et al, 2019).…”
Section: Discussionmentioning
confidence: 72%
“…Both red and white meat were reported to be among the most consumed products. We also observed a higher intake of red meat (pork, lamb, veal, beef) in CD patients compared to UC patients and higher intake of white meat (chicken, turkey, duck, rabbit) in UC patients than in CD patients, which should be further investigated because of the positive link between red and processed meat and GI cancers, such as gastric and colon cancer and colorectal cancer risk (Deoula et al, 2020;Kim et al, 2019), while white meat consumption is associated with a reduced risk of gastric cancer (Kim et al, 2019). In the latest Food and Crohn's Disease Exacerbation Study trial it has been noted that among patients with CD in remission, the level of red and processed meat intake was not correlated with time to symptomatic relapse (Albenberg et al, 2019).…”
Section: Discussionmentioning
confidence: 72%
“…Worldwide there has been a dramatic increase in the production of industrially processed foods which has coincided with a growing prevalence of obesity, metabolic disorders and multiple chronic diseases (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Global industrialisation, during which diets have been shifting from fresh unprocessed and minimally processed foods toward an increase in the consumption of "ultra-processed" foods (UPF), has been implicated as an important driver of these worrying trends in metabolic disease.…”
Section: Introductionmentioning
confidence: 99%
“…Using data from the 2011–2012 National Nutrition and Physical Activity Survey (NNPAS), Sui et al reported that red meat was consumed by 48.6% of Australian men and women, with beef as the most frequently reported type (41.8% and 34.7%, respectively) [ 30 ]. Some observational studies have found an association between consumption of beef and increased risk of a number of cancers [ 31 , 32 , 33 , 34 ]. Therefore, reducing beef intake and replacing it with plant-based proteins could be an effective strategy in the prevention of such conditions.…”
Section: Discussionmentioning
confidence: 99%